Research Progress on the Injury Mechanism and the Protective Effect of Blood-Brain Barrier - Yan, Han-Wen; He, Fang-Yan; Wang, Wei-Li; Liu, Li-Song; Lin, Qing; Duan, Xiao-Hua (International Journal of Biotechnology for Wellness Industries, 2015)
The Blood-Brain Barrier (BBB) is important structure to maintaining the stabilization of central nervous system. It is composed of endothelial cell and tight junction, the basal lamina, astrocytic endfeet. BBB’s injuries is a important symbol when central nervous system generate lesion in cerebral ischemical reperfusion injury (CIRI), its’ the injury mechanism including that matrix metalloproteinases’ activity raise induce that basal lamina and extracellular matrix degradation, the augmentation of Aquaporin-4’s expression cause vasogenic edema, destruction of tight junction and decrease of related protein expression lead to raise of BBB permeability, the adhesion molecules and cytokines stimulate the inflammatory reaction, a lot of free radicals production and nitric oxide toxicity can pose the damage of endothelial cells and basal lamina. BBB’s protection mainly by reducing the change of BBB’s morphological structure; decreasing BBB’s permeability; reducing the harmful substances go into BBB; maintaining stabilize of central nervous system’s internal environment. Now the mechanism was constantly expounded that BBB’s injury, adjustment and repair, more and more medicines will be applied to the prevention and treatment of the BBB. In this paper, we will review about research progress on the injury mechanism of BBB and the protective effect of it.